The art of the informal agricultural survey: IITA research guide, No. 36 - Rhoades, R.E. (1992)
The informal survey is cheap, practical and fast. It can give an accurate comprehension of local farming ecologies and practices. Informal surveys can be used for feasibility studies, for preparing formal surveys, and for direct planning of on-farm trials. This document gives some basic guidelines on how to conduct informal surveys.